Analisis Sentimen Pembatalan Indonesia Sebagai Tuan Rumah Piala Dunia FIFA U-20 Menggunakan Naïve Bayes - Harry Setiawan; Ilka Zufria (Universitas Budi Darma, 2023)
The FIFA U-20 World Cup is a prestigious event for young footballers around the world. Indonesia was originally to host the event in 2023, but FIFA eventually had to cancel the World Cup in Indonesia because some Indonesian public figures did not accept the presence of the Israeli national team in Indonesia at the football match. The refusal was made on security grounds, because the participation of the Israeli national team was considered a potential threat to Indonesia's security, especially considering the Palestinian conflict. Another reason, Indonesia does not have diplomatic relations with Israel, FIFA's decision is enough to cause a variety of opinions both positive and negative. The purpose of this research is to function so that people can be tabayyun by providing solutions by conducting sentiment analysis, namely collecting Twitter user opinions automatically so that they can be useful for the community. The data obtained is 946 tweets after going through the preprocessing stage then the data can be used in the labelling stage using the Lexicon Based method. Grouping is divided into positive sentiment and negative sentiment which is classified by the Naïve Bayes algorithm reinforced by Lexicon Based weighting resulting in positive sentiment as many as 150 tweets with a percentage of 15.86% and negative sentiment as many as 796 tweets with a percentage of 84.14%. From the confusion matrix results, the classification performance with the Naïve Bayes algorithm reinforced with Lexicon Based weighting then produces an accuracy percentage of 84%, with a precision of 86%, a recall of 95% and an f-measure value of 90%.